Tradycyjne dożynki kaszubskie w Gdyni-Cisowej. (Gdynia : [s.n.], 1946)
Afisz inf. o dożynkach, które miały miejsce 18.05.1946 r.
Keywords: Zrałek, Stanisław -- (1907-1954).; Święta rolnicze -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- źródła